The Influence of Norms and Consequences on Voluntary Catch and Release Angling Behavior - Stensland, Stian; Aas, Øystein; Mehmetoglu, Mehmet (Human Dimensions of Wildlife, 2013)
As catch and release angling (C&R) behavior increases, more knowledge is needed to understand the influence of norms and perceived consequences. Based on a survey of salmon anglers (n = 656) in Lakselv River, Norway, we showed that norms and awareness of consequences influence anglers’ behavioral intention of voluntarily releasing fish. Awareness of consequences had stronger impact on C&R behavior than the perceived social norm. The results from the structural modeling supported our initial conceptual model, and suggest that voluntary C&R is a process where the individual angler considers the biophysical (ecology, setting, species, status of stocks) and social setting in addition to other factors. Future research should look further into the cognitive part of obligation to do C&R, the more affective or emotional components of sanctions of doing or not doing C&R and the influence of knowledge, in different angler subpopulations and between types of fisheries. collective action, market segmentation, norms, path modeling, salmon fishing acceptedVersion This is an Accepted Manuscript of an article published by Taylor & Francis in Human Dimensions of Wildlife on 2013-09-05, available at http://www.tandfonline.com/doi/abs/10.1080/10871209.2013.811617